2023
DOI: 10.3389/fphar.2023.1168458
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of ferroptosis-related circular RNA in tumor metastasis

Abstract: Tumor metastasis is an important factor that contributes to the poor prognosis of patients with tumors. Therefore, to solve this problem, research on the mechanism of metastasis is essential. Ferroptosis, a new mode of cell death, is characterized by membrane damage due to lipid peroxidation caused by iron overload. Many studies have shown that excessive ferroptosis can affect tumor metastasis and thus inhibit tumor progression. Recently, circular RNA (circRNA), a type of non-coding RNA, has been shown to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 141 publications
0
1
0
Order By: Relevance
“…In recent years, circular RNA has been found to play an important regulatory role in various diseases through multiple signal transduction pathways ( Meng et al, 2023 ). The study conducted by Wu et al showed that inhibition of hsa_circ_0008870 could significantly suppress chondrocyte proliferation and endochondral ossification.…”
mentioning
confidence: 99%
“…In recent years, circular RNA has been found to play an important regulatory role in various diseases through multiple signal transduction pathways ( Meng et al, 2023 ). The study conducted by Wu et al showed that inhibition of hsa_circ_0008870 could significantly suppress chondrocyte proliferation and endochondral ossification.…”
mentioning
confidence: 99%